PENGARUH MEDIA VIDEO DAN POWER POINT TERHADAP PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DI PUSKESMAS ENGGANO BENGKULU UTARA - Heni Angraini (Jurnal Bidan Mandira Cendikia, 2022)
Based on the World Health Organization (WHO) in 2018 it was reported that every day 830 mothers in the world die from diseases/complications related to pregnancy and childbirth, 94% of all maternal deaths occur in low and middle to lower income countries. The danger signs of pregnancy that mothers must know start from the first trimester to the third trimester. studies say that other sources of information can be obtained through videos and power points. The use of various media is expected to accelerate the absorption of information about the danger signs of pregnancy. This study aims to determine the effect of video and power point media on the knowledge of pregnant women about the danger signs of pregnancy. This research is quantitative by using Quasi Experiment method with two group pretest-posttest design. The number of samples in the study were 18 pregnant women in the video group and 18 pregnant women in the power point group. Data collection was carried out using primary and secondary data. The results showed that there was an effect of video and power point media on the knowledge of pregnant women about the danger signs of pregnancy. It is hoped that with this research, health workers can pay more attention to the knowledge of pregnant women about the danger signs of pregnancy, by utilizing media such as videos, power points, and explanations related to understanding the information contained in the KIA handbook.